Pengaruh Earning Per Share (EPS), Price Earnings Ratio (PER), dan Return On Asset (ROA) Terhadap Harga Saham: Studi Pada Sub Sektor Kosmetik dan Keperluan Rumah Tangga Yang Terdaftar di BEI Periode 2016-2021 - Wulan Ayu Matovani; Ec Eko Widodo; Ahmad Idris (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
The influence of Earning Per Share (EPS), Price Earning Ratio (PER), Return on Assets (ROA) on stock prices is very important to know how much influence the independent variable has on the dependent variable. By knowing this influence, manufacturing companies in the cosmetics and household goods sector can further optimize the level of Earning Per Share (EPS), Price Earning Ratio (PER), Return On Assets (ROA) in the future. The sampling technique in this research used the purposive sampling method. The samples taken were in accordance with the criteria determined by the researcher. This research was conducted in 6 years from 2016-2021 on cosmetic and household goods manufacturing companies that conducted an IPO. Based on the research results, it shows that Earning Per Share (EPS) has a significant influence, Price Earning Ratio (PER) does not have a significant influence, Return On Assets (ROA) does not have a significant influence. Together the independent variables have a significant effect on the dependent variable, this is proven by the RÂ² value of 0.348 or 34.8%.